2015
DOI: 10.3390/ijms16035635
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms Underlying β-Adrenergic Receptor-Mediated Cross-Talk between Sympathetic Neurons and Immune Cells

Abstract: Cross-talk between the sympathetic nervous system (SNS) and immune system is vital for health and well-being. Infection, tissue injury and inflammation raise firing rates of sympathetic nerves, increasing their release of norepinephrine (NE) in lymphoid organs and tissues. NE stimulation of β2-adrenergic receptors (ARs) in immune cells activates the cAMP-protein kinase A (PKA) intracellular signaling pathway, a pathway that interfaces with other signaling pathways that regulate proliferation, differentiation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
158
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(161 citation statements)
references
References 133 publications
3
158
0
Order By: Relevance
“…However, we did not find any difference in IL-12 secretion between WT and IL-10 2/2 LPS-DC that had been treated with b 2 AR agonists, suggesting an IL-10-independent mechanism. b 2 AR belong to the G protein-coupled receptor family and are usually associated with the stimulatory subtype of G protein (G s ) (4,33). The canonical b 2 AR signaling pathway activation results in increased adenylyl cyclase activity that leads to augmented intracellular cAMP levels, which, in turn, promote PKA-mediated CREB phosphorylation (4,33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we did not find any difference in IL-12 secretion between WT and IL-10 2/2 LPS-DC that had been treated with b 2 AR agonists, suggesting an IL-10-independent mechanism. b 2 AR belong to the G protein-coupled receptor family and are usually associated with the stimulatory subtype of G protein (G s ) (4,33). The canonical b 2 AR signaling pathway activation results in increased adenylyl cyclase activity that leads to augmented intracellular cAMP levels, which, in turn, promote PKA-mediated CREB phosphorylation (4,33).…”
Section: Discussionmentioning
confidence: 99%
“…b 2 AR belong to the G protein-coupled receptor family and are usually associated with the stimulatory subtype of G protein (G s ) (4,33). The canonical b 2 AR signaling pathway activation results in increased adenylyl cyclase activity that leads to augmented intracellular cAMP levels, which, in turn, promote PKA-mediated CREB phosphorylation (4,33). Indeed, we found that b 2 AR activation in DC also results in increased cAMP levels and PKA-dependent CREB phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…These noradrenergic neurons provide innervation to all primary and secondary lymphoid tissues, including the bone marrow, spleen and lymph nodes (Jung et al, 2017; Nance and Sanders, 2007). Most immune cells express one or more type of adrenergic receptor (Table 1), but β 2 -adrenoceptors have the widest distribution and mediate most effects of sympathetic nerves on immune function (Bellinger and Lorton, 2014; Elenkov et al, 2000; Lorton and Bellinger, 2015; Padro and Sanders, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Most evidence indicates that activation of β 2 -adrenoceptors has immunosuppressive effects on monocytes and macrophages (Lorton and Bellinger, 2015; Padro and Sanders, 2014). However, these effects are context dependent, and pro-inflammatory responses can occur under some circumstances.…”
Section: Introductionmentioning
confidence: 99%
“…The sympathetic nervous system (SNS) communicates with all cells of the immune system, regulating their function through the release of norepinephrine (NE), and activating intercellular signaling pathway via the adrenergic receptors (ARs) expressed on immunocytes [13, 14]. Generally, TBI initially triggers an increase of SNS activity and exaggerated NE release, part of the host response to injury which can subsequently influence the immune function [15, 16].…”
Section: Introductionmentioning
confidence: 99%